Aplicación de la estrategia didáctica metalingüística para mejorar la ortografía en los estudiantes del 3er grado “A” de primaria en la I.E N°00654 Lucila Portocarrero Robalino de Vela - Dávila Maldonado, Reyna Isabel (2014)
Research on the implementation of the teaching strategy "Metalinguistic" to improve speUing in students of Grade "A" Primary Education in Educational lnstitution N o 00654 "Lucila Portocarrero Robalino Sail" from the city of Rioja has as aimed at improving student spelling Third Grade "A"; and specific were designing the teaching strategy "Metalinguistic" based on psycholinguistic theories, linguistic, cognitive psychology and sociocultural psychology; to plicate the teaching strategy "Metalinguistic" pre-level instruction, instruction and post co instruction; and evaluate the spelling in the dimensions of stress rules, use of capital letters, letters spellings and punctuation, level pre and post test. The teaching strategy "Metalinguistic" is based Fraca (2001}, Rada (2012}, and Fraca and Maurera (2006), who state that aims to develop language skills of the participants through the activation of knowledge about the speech and through awareness of comprehension and production processes; and spelling based on González and others (2009), Martínez et al (2005) and Matteoda and Vázquez (1992}, addressed as the process of teaching writing correctly with the correct use of the letters and auxiliary signs Writing . These theoretical assumptions lead to the following hypothesis: The application of the teaching strategy "Metalinguistic" significantly improve spelling in third grade students "A" Primary Education in Educational lnstitution N o 00654 "Lucila Portocarrero Robalino Sailing" city of Rioja. The research design used is applied, the sample consisted of 30 students of Grade "A" of School No. 00654 "Lucila Portocarrero Robalino Sailing". Regarding the hypothesis testing, the research hypothesis was accepted with a calculated valuetc = -11,449 and a tabular value t, = -1,699, verifying that the calculated value is less than the tabular value, which allows the null hypothesis is placed within the · rejection region.